Pengaruh konseling gizi dan penambahan makanan terhadap asupan zat gizi dan status gizi pasien HIV/AIDS - Yuniarti Yuniarti; Martalena Br Purba; Retno Pangastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Acquired Immunodeficiency Syndrome (AIDS) is a syndrome of opportunistic disease due to decreased immunity in patient HIV/AIDS with the symptom of losing weight progressively and low nutrition status. To cover the condition, it is necessary to give nutrition support. Objective: To compare the effect of nutrition counseling and nutrition supplementation with nutrition counseling only towards the nutrition status and nutrition intake of people living with HIV/AIDS (PLWHA).Method: The study was experimental non randomized control group pre-post test design. Subject consisted of two groups i.e. nutrition counseling plus (with nutrition supplementation) and nutrition counseling only. The study was carried out at Dr. Sardjito Hospital from January to March 2012. The sample were taken purposively with inclusion and exclusion criteria. Data were analyzed by using paired t-test and linear regression to calculate nutrient intake and nutrition status.Results: The energy intake of nutrition counseling plus group showed significantly higher amount than the group with nutrition counseling only (change of 141.40 kcal vs 15.99 kcal; OR=4.96). Protein intake was insignificantly higher than nutrition counseling (change of 6.28 g vs 5.11 g; OR=1.94), weight were insignificantly lower than nutrition counseling (change of 0.46 kg vs 0.75 kg; OR=1.21), and nutrition status were insignificantly lower than nutrition counseling (changes in body mass index 0.18 kg/m2 vs 0.32 kg/m2; OR=1.25).Conclusion: Nutrition counseling plus could increase energy intake but could not increase protein intake, weight, and body mass index.